2006
DOI: 10.1007/s11010-006-0433-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Terminalia arjuna bark extract on N-nitrosodiethylamine induced hepatocellular carcinoma in rats

Abstract: The present investigation was carried out to evaluate the antioxidant nature of ethanolic extract of Terminalia arjuna bark (EETA) on N-nitrosodiethylamine (DEN) induced liver cancer in male Wistar albino rats. Liver cancer was induced by single intraperitonial injection of DEN (200 mg/kg). After 2 weeks of DEN administration, Phenobarbital (PB) was given to promote the cancer for up to 14 successive weeks. EETA extract (400 mg/kg) was given post-orally for 28 days to hepatocellular carcinoma-bearing rats. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…There are reports which have showed that a single necrogenic DEN dose in rats decreased SOD and CAT activities after 7, 14, and 21 days. 40 In our study, DEN exposure showed a drastic alteration in liver morphology and serum ALT and AST activities, similar to detection by others studies. 34 In this work, IAA was shown to provide efficient protection on hepatic CAT and GR activities to the DEN effect and this auxin promoted a partial protection on the down-regulation of gene expression of antioxidant enzymes induced by DEN exposition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are reports which have showed that a single necrogenic DEN dose in rats decreased SOD and CAT activities after 7, 14, and 21 days. 40 In our study, DEN exposure showed a drastic alteration in liver morphology and serum ALT and AST activities, similar to detection by others studies. 34 In this work, IAA was shown to provide efficient protection on hepatic CAT and GR activities to the DEN effect and this auxin promoted a partial protection on the down-regulation of gene expression of antioxidant enzymes induced by DEN exposition.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, 4-ethyldeoxythymidine adduct accumulates in hepatocyte DNA following DEN administration which is thought to be important in tumor initiation. 19 There is extensive evidence that ROS participate in DENinduced hepatocarcinogenesis. 20 Recent work shows that indole compounds have been studied in vivo and in vitro as antitumor and chemopreventive agents, 4 but no studies have been reported on the protective effects of IAA on induced carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…20 The activity of Ca 2+ ATPase was assayed Group II-Disease control Received DEN at a single dose of 200 mg/kg (body weight) intraperitoneally on 1 st week followed by administration of phenobarbital (PB) (0.05% w/v) daily after 2 nd week through drinking water up to 16 successive weeks. 13,14 Group III-Treatment group Received DEN at a single dose of 200 mg/kg (body weight) intraperitoneally on 1 st week followed by administration of Phenobarbital (PB) (0.05% w/v) daily after 2 nd week through drinking water up to 16 weeks. Rutin was given orally after 2 nd week at a dose of 50 mg/kg, 15,16 (body weight) up to 16 successive weeks.…”
Section: 19mentioning
confidence: 99%
“…After A. ilicifolius extract treatment, the alterations in the levels of these enzymes were reverted back to near normal, which may be due to inhibition of glycolytic pathway and activation of gluconeogenesis. Thus, the plant extract may interrupt the energy requirement of tumor tissues and lead to the suppression of tumor growth (Sivalokanathan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%